Accelerating the EU's green transition - Borowiecki, Martin (OECD Economics Department Working Papers, 2023)
The EU's ambitious Green Deal aims at achieving net zero emissions by 2050. The EU is starting from a relatively good position. It has successfully reduced greenhouse gas emissions over the past decade. But further efforts are needed to reach the net zero target. These include an extension of emission trading to agriculture and the phase-out of generous subsidies for fossil fuels. Such efforts should be complemented by additional measures to shift to clean energy, notably more integrated electricity markets and deeper capital markets that provide the necessary investment in new technologies. Accelerating the green transition will also involve costs for displaced workers. Bolstering workers' mobility and training will help improve labour reallocation and reduce transition costs